Aspectos que influenciam no acesso de primeiro contato à atenção básica - Gueterres, Évilin Costa (2020)
According to current evidence, Primary Care services are essential in terms of the quality and resolution of health care, however, although this level of care is located in the territory of the subjects, there is fragmentation with regard to the access, a fact that needs improvement and qualification. With regard to the aspects that influence access to Primary Care services, there is a fragility in the national literature, which is still poorly evaluated and described the aspects that influence the quality of first contact access. In order to fill this gap, this dissertation was carried out with the purpose of evaluating the aspects that influence the access of first contact in Primary Care in municipalities of the 10th CRS / RS. With regard to the methodology, this is a cross-sectional descriptive study, using mixed methods, combining elements of a quantitative and qualitative approach. The research scenario was the Primary Care services in the municipalities of Fronteira Oeste / RS. As data source, variables belonging to the public database of the PMAQ-AB (2017/2018) were used, the data analysis was performed in a descriptive manner with absolute and relative frequency distribution. Regarding the qualitative phase, the coordinators of the Primary Care services were considered as subjects, the sample occurred intentionally and the data were collected through semi-structured interviews. Minayo's Operational Proposal was used as the method of analysis, including coordinators who had been in the service for more than 12 months. The results show that, although several aspects interfere in the quality of first contact access in Primary Care services, it is not possible to identify a single strategy for their qualification. It is noteworthy that the organization and systematization of processes with a focus on the needs of subjects and territories contributes to the reorganization of health care practices, and therefore access to Primary Care services. It is concluded that there are multiple actors involved in the qualification of first contact access, making possible the debate about the thematic, since all subjects are important for the construction and consolidation of SUS, which has access as one of its founding principles.